Formal and practical aspects of autonomic computing and networking : specification, development, and verification - Cong-Vinh, Phan (Hershey, PA : Information Science Reference)
"This book outlines the characteristics, novel approaches of specification, refinement, programming and verification associated with automated computing and networking"